The Charms of the Nature vs. Realities of People Living alongside the Water in Indonesian Poetry - Sitepu, Ied Veda (POETIKA, 2024)
In Indonesia, a country in which 70% of its area is water, people relate easily to both the sea and inland water, such as rivers and lakes. Authors consequently also find inspiration in these bodies of water, expressing their admiration towards the beauty of nature. For example, while they originate from different literary eras, “Danau Toba” (Lake Toba) by Sitor Situmorang, “Sepantun Laut” (Like the Sea) by J.E. Tatengkeng, “Akulah Si Telaga” (I am the Lake) by Sapardi Djoko Damono, “Apa Kata Bintang di Laut” (What the Star Tells the Sea) by Iwan Simatupang, “Kali Martapura” (Martapura River) by Hidjaz Yamani, and “Perempuan Pesisiran” (Women on the Coasts) by Iman Sembada all reflect the dynamic portrayals of water in Indonesian literature, as a charm of nature from each poet’s perspective or a framework for criticizing the realities of the lives of the people who live alongside water. This research analyzed these authors’ interconnectedness with nature, employing the qualitative descriptive method and using ecocriticism theory, which explores how nature is depicted in the respective poems and connects human relationships to nature. The results showed that the poets easily relate to the river, lake, or sea, and aside from describing the beauty of nature based on fond memories, their poems are used as critiques of the changing relationship between humans and nature, as well as between humans and humans. Their portrayals of nature further reveal the feelings of belonging engendered by water, which they use as criticism for the destruction of nature and societal changes stemming from the need for progress.